Compounds from the antioxidant active fraction of M. platytyrea - Nur Fadhilah Mohamad Haris,; Mohd Kamal Nik Hasan,; Ibtisam Abdul Wahab,; Mizaton Hazizul Hasan,; Thellie Ponto,; Aishah Adam, (Penerbit UKM, 2016)
This article discusses on the natural compounds from the ant plant (Myrmecodia species, family: Rubiaceae). The ethyl acetate (EtOAc) extract from the tuber of M. platytyrea was fractionated by using medium pressure liquid chromatography, giving eight fractions (F1-F8). Those fractions were evaluated using the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay. Fraction F5 was recorded as potent (EC50 = 21.57 ± 1.40 µg/mL). Then, it was purified by using column chromatography (CC) (mobile phase = chloroform: EtOAc). From the CC, ten fractions (F5F1-F5F10) were obtained and compound (1) was isolated from F5F3 via preparative thin layer chromatography (TLC). After spraying with anisaldehyde-sulphuric reagent, compound (1) gave a green TLC spot (Rf = 0.65, 100% CHCl3 , multiple development). The 1 H-Nuclear Magnetic Resonance (NMR) spectroscopy (500 MHz, CDCl3 ) was performed to determine the chemical framework of (1). This compound was identified as morindolide, having an iridoid structure. Meanwhile, the mass spectra for compounds (2) and (3) were analysed. The data presented the molecular ion at m/z 375 [M-H]- and 255, suggesting the formulation of 2-(2-methylbutyryl)phloroglucinol glucoside and a flavanone, respectively. From the literature, compound (1) was firstly isolated from a Chinese natural medicine, the dried root of Morinda officinalis (family: Rubiaceae). The flavonoids are also included as the biologically active compounds from Myrmecodia. In short, this is the first occurrence of morindolide from the ant plant.